A New Corrected Proof Sheet from Shakespeare's First Folio (1623). (10th March 2018) - Smith, Emma
Abstract: This note describes a sixth extant corrected proof sheet found in an Oxford copy of Shakespeare's First Folio (1623), and what it adds to the understanding of the printing process of King Lear .